AUDIT OF SPLENECTOMY AT JINNAH POSTGRADUATE MEDICAL CENTRE, KARACHI - Arshed, Mohammad Shahzad; Qureshi, Shamim; Channa, Asghar; Maher, Mumtaz (Journal of Ayub Medical College Abbottabad, 2011)
Objective: Splenectomy is often performed in patients with heamatalogical diseases or trauma who are at high risk of complications. Our aim is to perform an audit on splenectomy in order to determine the reasons for the operation, its complication and compliance with the recent recommendations for post-splenectomy patients at Jinnah Postgraduate Medical Centre. Design: It is a Descriptive study conducted in surgical ward 2 at Jinnah Postgraduate Medical Centre from June 2003 to June 2008. Methods: A retrospective review of hospital records of surgical ward 2 of consecutive splenectomy patients with a mean follow up of 12 months. Results: Fifty-five patients underwent splenectomy in 6 years duration. The mean age was 26.7 years. The indication for splenectomy was mainly heamatological diseases and trauma. Vaccination was done in 83.6% patients. Twelve patients had postsplenectomy complications, although there were no cases of OPSI. Mean hospital stay was 6.4 days. Conclusion: We still lack compliance with the standard guidelines for post-splenectomy patients. There is space for an improvement of the vaccination rate and prophylactic antibiotic. Patients should be counselled for the risk of OPSI and should have a splenectomised card for prompt treatment. There is need for careful documentation of this important health risk and counselling of patients in the discharge summaries. Keywords: splenectomy, pneumococcal, vaccination, antibiotic, prophylaxis